Thermal properties of PEDOT-compl-PSS sensor yarns and textile reinforced thermoplastic composites - Jerković, Ivona, tekstilna inženjerka (Array, 2019)
Smart textile structures such as sensor yarns provide real possibility for in situ structural health monitoring of textile reinforced thermoplastic composites. In this work thermal properties of E-glass/polypropylene (GF/ PP) and E-glass/poly(N,N’-hexamethylene adipamide) (GF/PA66) sensor yarns based on conductive polymer complex [3,4(ethylenedioxy)thiophene]-compl-poly(4-vinylbenzenesulfonic acid) (PEDOT-compl-PSS) and related composites were studied. Thermogravimetric analysis (TGA), microscale combustion calorimetry (MCC) and limiting oxygen index (LOI) methods were used to detect thermal behaviour of these structures and effect of coatings applied. According to TGA, GF/PP sensor yarn started to decompose at higher temperature, 345 °C, and showed higher pyrolysis residue, 28 %, compared to GF/PA66 sensor yarn that started to decompose at 316 °C and had lower pyrolysis residue, 23 % . The MCC showed that Heat Release Rate peaks of GF/PP sensor yarn, 341 W/g, and GF/PA66 sensor yarn, 348 W/g, occurred at similar Heat Release Temperature, ~ 430 °C. The additional peak, 51 W/g, was detected for GF/PP sensor yarn at 493 °C. Finally, LOI 22 and LOI 23 were detected only for GF/PP and GF/PA66 composites with integrated sensor yarns.